The structure and formation of business groups: Evidence from Korean chaebols - Almeida, Heitor; Park, Sang Yong; Subrahmanyam, Marti G.; Wolfenzon, Daniel (Journal of Financial Economics, 2011)
We study the evolution of Korean chaebols (business groups) using ownership data. Chaebols grow vertically (as pyramids) when the controlling family uses well-established group firms (“central firms”) to acquire firms with low pledgeable income and high acquisition premiums. Chaebols grow horizontally (through direct ownership) when the family acquires firms with high pledgeable income and low acquisition premiums. Central firms trade at a relative discount, due to shareholders’ anticipation of value-destroying acquisitions. Our evidence is consistent with the selection of firms into different positions in the chaebol and ascribes the underperformance of pyramidal firms to a selection effect rather than tunneling.